The Influence of Perceived Subjective Norms on Nurses' Hand Hygiene Behavior: Intention as an Intervening Variable - Rondhianto; Fitriani; Ismara Ketut Ima (Lembaga Penelitian dan Pengabdian Masyarakat Universitas dr. Soebandi, 2024)
Hand hygiene is one effort to reduce the risk of Healthcare-Associated Infections (HAIs). Nurses' compliance with hand hygiene is still low. The study aimed to analyze the influence of perceived subjective norms on nurses' hand hygiene behavior through intention as an intervening variable. The type of study is observational analytic with a cross-sectional design. The sample was nurses at Hospital X in Jember Regency (116 respondents) using a total sampling technique. The results show that most of the respondents were aged 26 – 35 years (52.59%), male (56.03%), had a diploma (43.97%), and had a working period of 1 – 5 years (39.66%). Model analysis showed the model fit with good predictive relevance (SRMR = 0.090; NFI = 0.851; Q2 = 0.608). Perceived subjective norms and intentions could explain hand hygiene behavior by 74.6% (R2 = 0.746; f2 = 0.146). Perceived subjective norms positively affected hand hygiene behavior directly (p = 0.001) and indirectly through intention (p = 0.001). Perceived subjective norms can increase nurses' hand hygiene intentions and compliance. Leaders of health institutions can improve the nurses' perceived subjective norms through regular monitoring and evaluation to increase hand hygiene intentions and behavior and reduce the risk of HAIs and patient mortality.